MODERN IDEAS ABOUT THE COMBINATION OF RADIATION THERAPY WITH ANTIANGIOGENIC DRUGS IN THE TREATMENT OF PATIENTS WITH BRAIN METASTASES - O. I. Kit; E. Yu. Gevorkian; Yu. S. Sidorenko; V. I. Voshedskiy; E. A. Genkova; A. V. Shaposhnikov; P. G. Sakun (Сибирский онкологический журнал, 2020)
Purpose of the study: to analyze available data on the combination of radiation therapy with antiangiogenic drugs in the treatment of patients with brain metastases. Material and methods. The search for relevant sources was carried out using Medline, Cochrane Library, Elibrary, PubMed databases concerning publications describing the role of radiation therapy in the treatment of patients with brain metastases. results. To date, there are various options for the combination of radiation therapy with antiangiogenic drugs. The results obtained indicate that radiotherapy combined with antiangiogenic drugs is more efficient in the treatment of patients with brain metastases than radiotherapy used alone. Conclusion. Treatment of patients with brain metastases remains extremely challenging and requires a multidisciplinary team approach.